PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO, DAN TOTAL ASSETS TURNOVER TERHADAP RETURN ON ASSETS PADA PERUSAHAAN KONSTRUKSI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sabri Nurdin; Yunus Tulak Tandirerung; Jayana Hurairah (Politeknik Negeri Samarinda, 2020)
This research aimed to investigate the impact among Current Ratio, Debt to Equity Ratio and Total Assets Turnover of Return On Assets at the construction companies listed in Indonesia Stock Exchange. There are two independent variables (X) used in this research, that is Current Ratio (X1), Debt to Equity Ratio (X2), and Debt to Assets Ratio (X3) while Return On Assets as the dependent variable (Y). The research population is the whole construction sector companies listed in Indonesia Stock Exchange. while the sampling used purposive sampling technique. Financial statement data collection form 2014 to 2018 used documentation techniques. The data collected were analyzed by the equation of each financial ratio, then processed by using classic assumption test, multiple regression analysis, coefficient of determination analysis, t-test and f-test. Based on the t-tes obtained result that the Current Ratio have positive and not significant influence to Return On Assets, Debt to Equity Ratio have negative and not significant influence to Return On Assets and Total Assets Tirnover have positive and significant influence to Return On Assets. While from the result of f-test obtained the Farithmetic is lower than the Ftable value (11,252 > 2,83) which means that simultaneously Current Ratio, Debt to Equity Ratio, and Total Assets Turnover have significant influence to Return On Assets. Keywords: Current Ratio, Debt To Equity Ratio, Total Assets Turnover, Return On Assets.